PRC2-Mediated Transcriptomic Alterations at the Embryonic Stage Govern Tumorigenesis and Clinical Outcome in MYCN-Driven Neuroblastoma - Tsubota, Shoma; Kishida, Satoshi; Shimamura, Teppei; Ohira, Miki; Yamashita, Satoshi; Cao, Dongliang; Kiyonari, Shinichi; Ushijima, Toshikazu; Kadomatsu, Kenji (Cancer research (Chicago, Ill.), 2017)
Pediatric cancers such as neuroblastoma are thought to involve a dysregulation of embryonic development. However, it has been difficult to identify the critical events that trigger tumorigenesis and differentiate them from normal development. In this study, we report the establishment of a spheroid culture method that enriches early-stage tumor cells from TH-MYCN mice, a preclinical model of neuroblastoma. Using this method, we found that tumorigenic cells were evident as early as day E13.5 during embryo development, when the MYC and PRC2 transcriptomes were significantly altered. Ezh2, an essential component of PRC2, was expressed in embryonic and postnatal tumor lesions and physically associated with N-MYC and we observed that H3K27me3 was increased at PRC2 target genes. PRC2 inhibition suppressed in vitro sphere formation, derepressed its target genes, and suppressed in situ tumor growth. In clinical specimens, expression of MYC and PRC2 target genes correlated strongly and predicted survival outcomes. Together, our findings highlighted PRC2-mediated transcriptional control during embryogenesis as a critical step in the development and clinical outcome of neuroblastoma. Cancer Res; 77(19); 5259–71. ©2017 AACR.